2012
DOI: 10.1097/icu.0b013e32834cd653
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for retinal detachment following cataract surgery

Abstract: Younger age, high myopia, and male sex continue to be associated with higher risk of pseudophakic retinal detachment. Intraoperative complications such as PCR also increase the retinal detachment risk. Given the high volume of cataract surgeries performed each year, pseudophakic retinal detachment contributes significantly to visual morbidity in the United States and Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 25 publications
0
52
2
1
Order By: Relevance
“…This could be related to the high prevalence of Retinal detachment is a serious complication after cataract extraction. The overall incidence of postoperative retinal detachment was estimated at about 0.7 % [10]. Studies reported high axial myopia as one of the risk factors for pseudophakic retinal detachment [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…This could be related to the high prevalence of Retinal detachment is a serious complication after cataract extraction. The overall incidence of postoperative retinal detachment was estimated at about 0.7 % [10]. Studies reported high axial myopia as one of the risk factors for pseudophakic retinal detachment [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…2 Retinal detachment (RD) after cataract extraction is a surgical visionthreatening event, with approximately half of patients not recovering better than 20/40 acuity. 3 The risk of RD after cataract surgery has been estimated at 0.7% 4 and increases up to 20 years after surgery. 5 As compared with the rate of 0.0065% to 0.079% for rhegmatogenous RD in the general population, 4,6 cataract surgery increases the risk of RD at least 4 fold, 4 and the absolute incidence of RD is substantial because of the large number of cataract surgeries performed.…”
mentioning
confidence: 99%
“…3 The risk of RD after cataract surgery has been estimated at 0.7% 4 and increases up to 20 years after surgery. 5 As compared with the rate of 0.0065% to 0.079% for rhegmatogenous RD in the general population, 4,6 cataract surgery increases the risk of RD at least 4 fold, 4 and the absolute incidence of RD is substantial because of the large number of cataract surgeries performed. 7 Cataract surgery continues to improve, with reduced incision size and multifocal lens technologies.…”
mentioning
confidence: 99%
“…Loss of the vitreous during cataract surgery is considered to be a factor increasing the risk of RD to 4.9% [14]. Also posterior capsule rupture, anterior vitrectomy, high myopia, younger age, and male sex have been found -in large studies -to be predisposing factors for RD after cataract surgery [15][16][17]. YAG capsulotomy is considered as an important risk factor for RD in some studies [18,19], but other studies failed to confirm this finding [20].…”
Section: Discussionmentioning
confidence: 99%